Kombinasi Teknik Relaksasi Benson dan Aromaterapi Lavender dalam Menurunkan Nyeri dan Ansietas pada Pasien Lansia dengan Closed Fracture of Neck Femur Dextra: Sebuah Studi Kasus: The Combination of Benson Relaxation Technique and Lavender Aromatherapy in Reducing Pain and Anxiety in Elderly Patients with Closed Fracture of the Right Femoral Neck: A Case Study - Agusni, Wulan; Kurnia, Gian M.; Susilawati, Susilawati; Suku, Alexander Mela Geniko (Chakra Brahmanda Lentera Institute, 2026)
Background and Objectives: Elderly patients with hip fractures often experience severe pain and anxiety, which can impede recovery. Non-pharmacological interventions such as Benson's relaxation and lavender aromatherapy have shown potential in managing these symptoms, but evidence of their effectiveness in geriatric orthopedic settings remains limited. This case study aimed to evaluate the effects of a combination of both therapies on pain, anxiety, mobility, and vital signs in a geriatric patient following hip fracture surgery. Methods: This study used a single-subject case study design. The sample was a 72-year-old female diagnosed with a closed fracture of the right femoral neck post-hip replacement surgery. The combined intervention of Benson's relaxation (twice daily, 15 minutes) and lavender aromatherapy inhalation (twice daily, 30 minutes) was administered for four days alongside standard care. Measured variables included pain intensity (numerical rating scale 0-10), anxiety level (Hamilton Anxiety Rating Scale / HARS), lower extremity joint range of motion (ROM scale 0-5), and vital signs (blood pressure, pulse, respiration). Data collection instruments comprised observation sheets, the HARS questionnaire, and a numerical pain scale. Main Results: After four days of intervention, significant reductions were observed in pain intensity (from 5/10 to 2/10) and HARS anxiety scores (from 30 [severe] to 9 [mild]). Patient mobility improved, as indicated by an increase in lower extremity ROM from 3/5 to 4/5. Vital signs (blood pressure, pulse, respiration) showed a stabilizing trend within the normal range. No adverse effects or undesirable events were reported during the intervention period. Conclusion: Based on the findings, the combination of Benson's relaxation and lavender aromatherapy was effective in reducing pain and anxiety, improving mobility, and stabilizing vital signs in a geriatric patient post-hip fracture surgery. This combined therapy is safe and has the potential to be integrated as a complementary, evidence-based perioperative management strategy for the geriatric population in orthopedics. Further studies with more robust designs and larger samples are needed to generalize these findings.